2012
DOI: 10.2172/1056168
|View full text |Cite
|
Sign up to set email alerts
|

Review and Assessment of Commercial Vendors/Options for Feeding and Pumping Biomass Slurries for Hydrothermal Liquefaction

Abstract: This document was printed on recycled paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 2 publications
1
25
0
Order By: Relevance
“…%. This range falls within the existing commercial slurry pump-ability range [17,42,50] and based on recent life cycle assessment studies reported in literature for hydrothermal processing, would result in a net positive-producer/energy valorization system [12,42,[47][48][49][51][52][53][54].…”
Section: Algal Biomass Case Studymentioning
confidence: 95%
See 2 more Smart Citations
“…%. This range falls within the existing commercial slurry pump-ability range [17,42,50] and based on recent life cycle assessment studies reported in literature for hydrothermal processing, would result in a net positive-producer/energy valorization system [12,42,[47][48][49][51][52][53][54].…”
Section: Algal Biomass Case Studymentioning
confidence: 95%
“…Aside from eluding pumping challenges and clogging during slurry processing, the physical pretreatment steps lead to increased accessibility to the organic pores, and as a result enhanced hydrolysis and fragmentation. The slurry is then pressurized to 250 bar by means of a five stage rotary lobe pumping system, selected from a compiled list of commercial vendors available in literature [50], and then further preheated to 350 • C.…”
Section: Common Upstream Syngas Production Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…The AUXWATER stream is simulated as pure water, however, it is envisaged in the plant assessment as a mixture of recycled aqueous stream from the wastewater treatment plant (not modelled) and 10% make-up water. The plant input solid content is a conservative design condition, estimated for feasible pumping capabilities of lignocellulose slurries (maximum 18 wt.% solids) reported from commercial vendors and compiled in [36]. The mixture enters a pre-treatment step modelled in Aspen Plus ® as simply a mixer, while the overall plant evaluation accounted for the specified utility demands based on [37].…”
Section: The Hydrothermal Liquefaction Aspen Plus ® Modelmentioning
confidence: 99%
“…The pre-treated slurry is then fed into the pumping stage were the slurry is upgraded over five sequential stage pumps of maximum 50 bar each. The pump system design is based on the rotary lobe pump system developed by Zeilfelder Pumpen GmbH [36]. Advantageous features of the pump are the upper temperature limits of 350 °C, which would allow booster operation at reactor inlet conditions.…”
Section: The Hydrothermal Liquefaction Aspen Plus ® Modelmentioning
confidence: 99%